Effect of the Magnetic Force on Ferrite Pendulum Oscillation Parameters: Parametric Analysis on Ferrite Pendulum - Rusli Adi; Moh Toifur; Ishafit Ishafit; Rosly Jaafar (Universitas Ahmad Dahlan, 2020)
The magnitude of the damping force of the mathematical pendulum swinging on a medium is usually proportional to the speed of the pendulum. In this research, the pendulum oscillation parameters oscillating on an air medium under the influence of a magnetic field of 1.8 G will be investigated. In the initial stage, the effect of the magnetic force on the damping coefficient of ferrite pendulum oscillations with an initial deviation of 15 degrees observed. Furthermore, the study continued with varying the angle of deviation from 5 degrees to 25 degrees. The results of the data fitting amplitude (xi) at various swing times (ti) are using to analyze the effect of the angle of deviation on the maximum amplitude. The results showed that for the deviation angle of 15o the coefficient of damping of the medium affected by the magnetic force was 0,0022 greater than the coefficient of air damping 0,00006. It affects the amplitude, which decreases faster than the pendulum amplitude without the influence of magnetic force. Variation in the angle of deviation also affects the amplitude of the pendulum. In the deviation angle below 10, the pendulum motion is more influenced by the magnetic force, whereas in the deviation above 10, the pendulum motion is more dominated by gravity.